2006
DOI: 10.1021/bi060893t
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Studies on the Mononuclear ZnII-Containing Metallo-β-lactamase ImiS from Aeromonas sobria

Abstract: In an effort to understand the reaction mechanism of a B2 metallo-β-lactamase, steady-state and presteady state kinetic and rapid-freeze quench EPR studies were conducted on ImiS and its reaction with imipenem and meropenem. pH Dependence studies revealed no inflection points in the pH range of 5.0 -8.5, while proton inventories demonstrated at least 1 rate-limiting proton transfer. Sitedirected mutagenesis studies revealed that Lys224 plays a catalytic role in ImiS, while the side chain of Asn233 does not pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
90
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(100 citation statements)
references
References 57 publications
9
90
1
Order By: Relevance
“…The calculated activation free energy for the reaction is in good agreement with experimental findings, and the proposed mechanism is consistent with the studies by Crowder and coworkers (30), who showed that the rate-limiting step is the C-N ␤-lactam cleavage and involves a proton transfer event. The catalytic mechanism is also consistent with previous experimental (52) and theoretical (22) studies, while pointing to the presence of a second water molecule in the active site as crucial element for an efficient ␤-lactam hydrolysis.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The calculated activation free energy for the reaction is in good agreement with experimental findings, and the proposed mechanism is consistent with the studies by Crowder and coworkers (30), who showed that the rate-limiting step is the C-N ␤-lactam cleavage and involves a proton transfer event. The catalytic mechanism is also consistent with previous experimental (52) and theoretical (22) studies, while pointing to the presence of a second water molecule in the active site as crucial element for an efficient ␤-lactam hydrolysis.…”
Section: Discussionsupporting
confidence: 89%
“…However, this hypothesis is not consistent with experimental studies by Crowder and co-workers (30), who have shown that the reaction catalyzed by the B2 M␤L ImiS from Aeromonas veronii bv. Sobria is characterized by a rate-determining proton transfer step.…”
contrasting
confidence: 67%
“…In one of them Table S1. involves the Zn2 ion) (16,17,46,48). This suggests that a strategy aimed for the design of a general inhibitor could be pursued by targeting the Zn2 site.…”
Section: Gob-18mentioning
confidence: 99%
“…The issue that remains unsolved is the identification of the nucleophile in Zn2-only enzymes. The absence of the Zn1 site in B2 lactamases has led to the proposal of a non-metal activated nucleophile, a hypothesis later supported by theoretical and enzymological studies (48,49). However, the possibility of a Zn2-bound nucleophile cannot been definitively ruled out.…”
Section: Gob-18mentioning
confidence: 99%
“…[60] Initially, a reduced number of structures of B2 MβL, CphA from Aeromonas hydrophila, [61] ImiS from Aeromonas veronii bv. Sobria [62] and Sfh.I from Serratia fonticola, [60] have been cristalyzed, being the CphA the most studied one. In particular, three different structures, two of them in the apo form and the last one corresponding to the N220G mutant in complex with a biapenem (BIA) derivative, were obtained.…”
mentioning
confidence: 99%